Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970 - Adie, Raymond J. (International Union of Geological Sciences, 1972)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Fossile virveldyr fra Antarktis - Heintz, Natascha (Naturen, 1972)
Keywords: Antarktis; paleontologi

Diurnal variations of the surface wind over the Antarctic ice shelf - Hisdal, Vidar (Norsk Polarinstitutt. Årbok 1970, 1972)
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

Diurnal wind variations in Antarctica - Hisdal, Vidar (Quarterly Journal of the Royal Meteorological Society, 1972)
For the three Antarctic ice shelf stations considered (Norway Station, Maudheim, and Halley Bay) it is shown that from spring to autumn a systematic diurnal variation of the mean vector wind at the surface exists. Different factors that may be responsible for this variation are discussed. The results seem to agree well with the assumption that in areas far from the ice front (the seaward edge of the ice shelf) the main cause is the larger net gain of momentum in the lowest layers during the middle of the day, while closer to the ice front there is an additional effect of the varying contrast between the air temperature over the sea and over the ice shelf.
Keywords: Antarktis; Dronning Maud Land; glasiologi; meteorologi

A 200-Year Record of Glacier Mass Balance at Deception Island, Southwest Atlantic Ocean, and Its Bearing on Models of Global Climatic Change - Orheim, Olav (The Ohio State University, 1972)
Keywords: Antarktis; ekspedisjoner; glasiologi; isbreer; klimaendringer; meteorologi; storbreen; stratigrafi